Study of computed tomography perfusion In traumatic brain contusion - Karim, Ahmad Helmy Abdul (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2013)
Background: Brain ischaemia and infarction are the leading factors in morbidity and mortality of traumatic brain injury. TI1is study aimed to determine the perfusion status of pericontusional hypodense areas in traumatic cerebral contusion Method: Ten patients involved in motor vehicle accidents were enrolled in this study, and contusions were diagnosed from plain computed tomography scans of the brain. Subsequent computed tomography perfusion (en>) was performed to analyse the perfusion ofpericontusional hypodense areas, whicll were divided into 4 regions of interest (ROI). Results: Most ischaemic perfusion was found in ROI 6 (affecting 60% of patients), although the mean of the perfusion parameters were normal. A significant positive correlation was fonnd between the perfusion status in the pericontusional area nearest to the skull vault (ROI 3) and its distance/thickness to the skull vault (r = 0.698, P = 0.025). Two adjacent pericontusional hypodense areas (ROI 4 and ROI 5) showed a significant positive correlation with eacll other (r = 0.667, P = 0.035) in terms of perfusion status. The presence of a hypodense pericontusional area is suggestive of oedema and perfusion disturbances. Conclusion: en> is a useful, fast, and appropriate method in evaluating perfusion of pericontusional hypodensity area that may help the treating physician to provide an appropriate treatment to the patient.